Identifying the Indicators of Trust for Strategic Collaborative Buyer Supplier Relationships - van der Nest, Nicolas (Curtin University, 2021)
The research focuses on identifying the indicators of trust that enable the signalling of trust behaviours within strategic collaborative buyer-supplier relationships. The thesis utilised a mixed-methods approach to identify the indicators of trust, which included content analyses of newspaper media & peer-reviewed journal papers and interviews with industry experts. The research findings provide organisations with the tools to help them to signal trust behaviours to a counterpart in a collaborative buyer-supplier relationship.